Deconvolution of distinct lithology chemistry through oversampling with the Mars Science Laboratory Alpha Particle X‐Ray Spectrometer. (5th February 2016) - VanBommel, Scott J.; Gellert, Ralf; Berger, Jeff A.; Campbell, John L.; Thompson, Lucy M.; Edgett, Kenneth S.; McBride, Marie J.; Minitti, Michelle E.; Pradler, Irina; Boyd, Nicholas I.
Abstract : The Alpha Particle X‐Ray Spectrometer (APXS) determines the chemical composition of Martian rocks and soils on‐board both activeNational Aeronautics and SpaceAdministration (NASA) rovers using X‐ray emission spectroscopy through complementary particle‐induced X‐ray emission (PIXE) and X‐ray fluorescence (XRF) excitation methods. A single APXS spectrum represents the sum of the signals from within the instrument's field of view (FOV). In the past, features smaller than the FOV have been investigated through repeated measurements with stepwise lateral offsets. These lateral offsets allow for empirically extracting, through elemental correlations, distinct compositions of different features. Here, we present a novel analytical method for deconvolving the endmember chemistry of visually distinct components through oversampling and the integrated analysis of the elemental data and supporting images. We discuss specifically the method's application to three targets investigated by the Mars Science Laboratory rover Curiosity during its traverse, as well as the added information that can be gained from this method in the future. Copyright © 2016 John Wiley & Sons, Ltd.